2019
DOI: 10.1111/anti.12510
|View full text |Cite
|
Sign up to set email alerts
|

Financialisation, Climate Finance, and the Calculative Challenges of Managing Environmental Change

Abstract: This article describes the emergent and unstable dispositif of climate finance that is being built from iterative experiments in climate finance provision. The article provides a periodisation of different phases of climate finance from the 1990s onward using examples from REDD+, ecosystem services, the Green Climate Fund, green bonds, and insurance‐based derivatives, and connects this periodisation to broader processes of financialisation. It analyses how climate finance projects incorporate competing systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 49 publications
(62 reference statements)
0
70
0
3
Order By: Relevance
“…As they effectively hold a slice of the overall market, their investment returns will depend on the social, environmental and financial sustainability of the overall economy (Hawley and Williams 2000 , 2007 ; Monks 2001 ). On the other hand, more critical scholars have suggested that this view of sustainable finance is overly optimistic, maintaining that finance is unable to offer real solutions to the sustainability challenges that we are facing (Fletcher 2012 ; Klein 2014 ; Bracking 2019 ). It has been argued that even the current climate disaster has been exploited for financial gains (Büscher et al 2014 ).…”
Section: The Rise Of Sustainable Finance: An Institutional Logics Permentioning
confidence: 99%
See 2 more Smart Citations
“…As they effectively hold a slice of the overall market, their investment returns will depend on the social, environmental and financial sustainability of the overall economy (Hawley and Williams 2000 , 2007 ; Monks 2001 ). On the other hand, more critical scholars have suggested that this view of sustainable finance is overly optimistic, maintaining that finance is unable to offer real solutions to the sustainability challenges that we are facing (Fletcher 2012 ; Klein 2014 ; Bracking 2019 ). It has been argued that even the current climate disaster has been exploited for financial gains (Büscher et al 2014 ).…”
Section: The Rise Of Sustainable Finance: An Institutional Logics Permentioning
confidence: 99%
“…It has been argued that even the current climate disaster has been exploited for financial gains (Büscher et al 2014 ). They tend to emphasise the structural negative implications of financialisation on society and the environment and the inherent unsustainability of dominant neoliberal financial logics (Speth 2009 ; Krippner 2011 ; Lazonick 2014 ; Lagoarde-Segot 2019 ; Bracking 2019 ). For instance, Lagoarde-Segot ( 2019 ) maintains that there are epistemological, ontological and methodological tensions separating standard financial theory from truly sustainable finance.…”
Section: The Rise Of Sustainable Finance: An Institutional Logics Permentioning
confidence: 99%
See 1 more Smart Citation
“…The second political concern emerges from scholarship on value and risk in the green bond market. This analysis has primarily focused on the relation between risk and surplus value (Christophers, 2018b); the way risk may coordinate multiple units of value in the green economy (Bracking, 2019); as well as the (re)constitution of risk across different scales and social groups (Bigger and Millington, 2019;. The chief political concern raised here is that green bonds may amplify social inequality.…”
Section: Amplifying Inequalitymentioning
confidence: 99%
“…Using blockchain to bring trust to these transactions risks maintaining pre-existing North-South trade and investment flows and neo-colonial geographies of inequality that render much of the global south increasingly marginalized. Scaling up green debt markets in Africa restricts the organic growth of green enterprises as they risk their returns disappearing to international investors, whose income may be guaranteed by public sector entities (Bracking, 2019). The most environmentally-effective solution for companies and individuals with high carbon footprints, whose sites of production are located in the Global North, is obvious -prevent excessive pollution at source.…”
Section: Blockchain For Clean Developmentmentioning
confidence: 99%